Kandidiasis Vulvovaginalis dan Kondiloma Akuminata : Laporan Kasus pada Anak - Mareta, Cindy Ayu; Angraini, Dwi Indria (CV. Jasa Sukses Abadi, 2024)
Vulvovaginal candidiasis (CVV) and condyloma acuminata (KA) are sexually transmitted infections (STIs) that are frequently reported. KVV is generally caused by Candida albicans. KA is caused by Human Papilloma Virus (HPV) 6 and 11. The incidence of KA in children has increased in the last few decades. This case report aims to report cases of KVV and KA in children. A 13 year old girl came to the skin and genital clinic at Dr. RSUD. H. Abdul Moeloek, Lampung Province with complaints of white, lumpy and itchy vaginal discharge since 1 month ago. On physical examination, venerological status revealed diffuse erythematous lesions with satellite lesions on the labia majora. In the vulva there is a moderate amount of lumpy, rice-like discharge. In the vulva to perianal region, multiple verrucous papillomatosis papules appeared with positive acetowhite test results. The results of KOH examination of vaginal secretions showed Candida sp. The patient's therapy was given systemic fluconazole and cetrizine, as well as topical myconazole nitrate cream. In this case, there was clinical improvement in CVV after systemic and topical antifungal therapy.